The Effect of Sentencing on Women, Men, the Family, and the Community - Weinstein, Jack B. (Columbia Journal of Gender and Law, 1996)
There are two provisions in the Federal Sentencing Guidelines (“Guidelines”) that make no sense in the real world: one dictates that sex-along with race, national origin, and other factors-is not relevant to sentencing. The other asserts the “general inappropriateness” of considering “family ties and responsibilities” in determining the term of imprisonment. The first provision is merely inappropriately worded. Of course these factors may be relevant. In my opinion, what the Sentencing Commission means is that sex and such factors should not be used in a biased way. The second provision is so cruelly delusive as to make those who have to apply the guidelines to human beings, families, and the community want to weep. Family ties and responsibilities must be considered. The effect of removing a single caretaker-nurturer from dependent family members needs to be seriously considered. Even with respect to two-parent families, the harmful effects of destroying a stable family, particularly now that the widespread prevalence of dysfunctional families threatens to tear apart our social fabric, must be taken into account.